O uso das medicinas tradicionais entre comunitários do Bairro do Mapiri, Santarém/Pa: um relato de experiência - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
This study addresses the use of traditional medicine for health care among community members in the Mapiri neighborhood, in the municipality of Santarém, State of Pará, Brazil. The objective was to investigate the continuity of the use of traditional medicines among local residents. For this purpose, 98 participants were interviewed in the period from 2020 to 2022. The data obtained were stored in the E-SUS Território program made available to Community Health Agents. It was observed that of the 98 interviewees, 64 use traditional medicines, with a predominance of women aged between 21 and 50 years. Among the various types of traditional medicine available, medicinal plants, healers, dismintidura handlers, herbal medicines, healers and midwives are used by the Mapiri community. Thus, it is concluded that the use of traditional knowledge is still very evident among the interviewed community members for the care of themselves and their families.
Keywords: Medicinas Tradicionais; Mapiri; Agente Comunitário; CNPQ:: CIÊNCIAS DA SAÚDE